How Does Framing Strategy Affect Evaluation of Culturally Mixed Products? The Self–Other Asymmetry Effect. (November 2016) - Cui, Nan; Xu, Lan; Wang, Tao; Qualls, William; Hu, Yanghong
The article examines the effect of bicultural framing strategy on the evaluation of culturally mixed products (CMPs). Across two experiments, we demonstrate a self–other asymmetry effect in the CMP evaluation. Specifically, we examine the "foreign-culture home-culture" strategy in which the foreign culture "modifies" the home culture. This phenomenon leads to less favorable evaluation of CMPs relative to the "home-culture foreign-culture" strategy in which the home culture "modifies" the foreign culture. Furthermore, the findings show that consumers' perception of cultural intrusion mediates the effect of framing strategy on CMP evaluation. We also identify the boundary condition wherein the self–other asymmetry is attenuated when people focus their judgment on facts (as opposed to motivation).